Analisis Kesiapan Jurnal Akademik di Lingkungan Universitas Tidar menuju Bereputasi Nasional - Nina Agustyaningrum; Eka Nur Jannah; Khairul Ikhwan (Jurnal Pustaka Ilmiah, 2024)
Scientific journals are crucial for disseminating research and providing up-to-date references in various fields.  As such, any research that does not refer to current and relevant journals will lose its significance and novelty. Therefore, earnest efforts are necessary to produce quality journals, particularly within higher education institutions. This study aims to analyze the readiness of journals at Tidar University to achieve accreditation as nationally reputable journals through SINTA accreditation. The analysis refers to the instruments and criteria required by the national journal accreditation system (ARJUNA). This research is a descriptive quantitative study using a literature review method by conducting an online search of journal websites. The collected information is analyzed using content analysis methods to obtain information on the readiness of the journals according to the scientific journal accreditation guidelines. Findings indicate that out of 34 journals at Tidar University, 24 (70%) are unaccredited. These unaccredited journals have the potential to pursue accreditation. Journals meeting accreditation requirements include the Journal of Aquaculture Development and Environment (JADE), Journal of Livestock Science and Production (JaLSPro), THETA OMEGA: Journal of Electrical Engineering, Computer, and Information Technology, Jurnal Rekayasa Infrastruktur Sipil, ABDIPRAJA, and Jurnal Pengabdian Masyarakat (KASTARA). Other journals need to fulfill requirements such as obtaining a DOI, having two years of publication history, and Google Scholar indexing. Based on these findings, the university should support by providing training and mentoring for journal editors to improve management, thereby achieving national accreditation.